2021
DOI: 10.1093/ptj/pzab298
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 2 Different Dual-Task Balance Training Methods on Balance and Gait in Older Adults: A Randomized Controlled Trial

Abstract: Objective The purpose of this study was to compare the effects of integrated and consecutive cognitive dual-task balance training in older adults on balance, fear of falling, and gait performance. Methods Fifty-eight subjects (age > 65 years) were randomly assigned to an integrated dual-task training group (IDTT) (n = 29) and consecutive dual-task training group (CDTT) (n = 29). Balance exercises and cognitive tasks we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…The DT interventions delivered in the included studies were (1) motor-cognitive, (2) motor-motor, or (3) cognitive–cognitive DT, as reported in Table 1 . Among the 30 included studies, 22 studies [ 21 , 22 , 29 , 44 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] used motor-cognitive DT training, 6 [ 23 , 28 , 30 , 45 , 59 , 64 ] used a motor-motor type of task, and 2 [ 65 , 66 ] included cognitive exercise in both tasks.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The DT interventions delivered in the included studies were (1) motor-cognitive, (2) motor-motor, or (3) cognitive–cognitive DT, as reported in Table 1 . Among the 30 included studies, 22 studies [ 21 , 22 , 29 , 44 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] used motor-cognitive DT training, 6 [ 23 , 28 , 30 , 45 , 59 , 64 ] used a motor-motor type of task, and 2 [ 65 , 66 ] included cognitive exercise in both tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Across the 30 included studies, different types of exercises were applied. Balance exercises appeared most frequently, as they were used in 12 studies [ 21 , 22 , 30 , 47 , 50 , 51 , 54 , 58 , 61 , 62 , 63 , 64 ]. Balance exercises were performed using free-hand, low-tech systems with minimal technology support or technology-dependent, computerized balance systems.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations